2015
DOI: 10.3905/jii.2015.6.1.017
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of Smart Beta Strategies

Abstract: Lack of robustness in smart beta strategies can be caused mainly by exposure to four different risks in the strategy construction process: factor fishing, model mining, nonrobust-weighting schemes, and strong factor dependencies. If the first three factors can have a major inf luence on the relative robustness, the last is at the heart of the issue of absolute All statistics are annualized and daily total returns in USD are used for the analysis. The "Secondary Market U.S. Treasury Bills (3M)" is the risk-free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Ledoit, Wolf, and Zhao (2019) and Hsu, Kalesnik, and Surti (2010) have shown that factor underperformance may be tackled by using more sophisticated weighting criteria. Amenc et al (2015) also recognise that index providers do not always efficiently deal with the issue of ensuring out-of-sample robustness of factor investing strategies. They suggest certain practices that index creators can follow to improve the robustness of factor portfolios.…”
Section: Resultsmentioning
confidence: 99%
“…Ledoit, Wolf, and Zhao (2019) and Hsu, Kalesnik, and Surti (2010) have shown that factor underperformance may be tackled by using more sophisticated weighting criteria. Amenc et al (2015) also recognise that index providers do not always efficiently deal with the issue of ensuring out-of-sample robustness of factor investing strategies. They suggest certain practices that index creators can follow to improve the robustness of factor portfolios.…”
Section: Resultsmentioning
confidence: 99%
“…Smart betas create new markets and their ultimate goal is to deliver superior performance. Amenc et al (2015) evaluate the robustness of various smart beta strategies and suggest that single-factor indices have high robustness only in similar market conditions, while multi-beta allocations have high robustness regardless of prevailing market conditions. However, Malkiel (2014) argues that the excess returns generated by smart beta funds are compensations of the additional risks they assume.…”
Section: Introductionmentioning
confidence: 99%
“…The robustness of treating factors as investable indices, presented as a reasonable alternative to cap-weighted indices has been evaluated by e.g. Amenc et al [2015]. Cazalet, Grison and Roncalli [2013] evaluated construction of "smart beta" indices based on risk factors.…”
Section: Introductionmentioning
confidence: 99%